Lipid Assemblies as Tools for Drug Delivery - Anju, Gupta (International Journal of Lipids, 2020)
This review discusses lipid assemblies—from liposomes to solid lipid nanoparticles—as platforms for drug delivery. It covers design principles, targeting strategies, and manufacturing considerations.
Keywords: Lipid